Preparation and characterization of polylactic acid based polyurethane for environmental friendly packaging materials - Ismail , Muhamad Norshafiq; Rafidi, Najihah; Ali, Fathilah (Kulliyah of Engineering, International Islamic University Malaysia, 2016)
‘Green, versatile, and Sustainable’ make palm oil (PO) an excellent source to be used in polyurethane (PU) especially for commercialization. Vegetable oil-based polyols are used in many productions of PU including palm oil-based (PO) polyol. Polyol can be polymerized through urethane linkages with biodegdable polymer. Polylactic acid (PLA) is a type of biodegradable polymer which is brittle but has good mechanical strength, which makes it a suitable polymer to be used in synthesis of polyurethane for green packaging material. PO polyol was used as soft segments to improve the brittleness and flexibility of PLA and hexamethylene diisocyanate (HDI) is source of isocyanate. PLA/Palm oil based polyurethane (PLAPOPU) was synthesized using one-shot polymerization process at predetermined ratio to achieve optimum physical properties. This polymerized PLAPOPU has high potential to be used in environmental friendly packaging industries.